Opinions on Marijuana: Sex Differences at a Western Canadian University - Taylor, Hugh (Canadian Journal of Counselling and Psychotherapy, 1972)
Three hundred and seventy-two freshmen at the University of Victoria were surveyed to determine their opinions regarding the following four aspects concerning marijuana. 1. Whether marijuana is a beneficial or dangerous substance. 2. Types of legal controls that should be placed on the substance. 3. Each student's estimate of future use of marijuana and 4. The ease of obtaining the substance.Chi-square analysis of the data showed that in the sample surveyed male students in all cases were ahead of female students in exploring the marijuana sub-culture. The data provides a basis for judging future trends in this controversial area of student life.